Self-care in heart failure patients - Ana Paula da Conceição; Mariana Alvina dos Santos; Bernardo dos Santos; Diná de Almeida Lopes Monteiro da Cruz (Universidade de São Paulo, 2015)
AbstractObjective: to describe self-care behavior and its associated factors in a sample of heart failure Brazilian patients.Method: descriptive cross-sectional study with non-probabilistic sample of 116 ambulatory patients undergoing heart failure treatment. Self-care was evaluated using the Self-Care of Heart Failure Index, (scores ≥70 points=appropriate self-care). Association tests were applied, considering a descriptive level of 0.05.Results: the mean age of participants was 57.7 (SD =11.3) years; 54.3% were male; the mean schooling was 5.5 (SD = 4.0) years; and 74.1% had functional class II-III. The mean scores on the subscales of the Self-Care of Heart Failure Index indicated inappropriate self-care (self-care maintenance: 53.2 (SD =14.3), selfcare management: 50.0 (SD = 20.3) and self-care confidence: 52.6 (SD=22.7)) and it was found low frequencies of participants with appropriate self-care (self-care maintenance, 6.9%), self-care management (14.7%) and self-care confidence (19%). Higher scores of the Self-Care of Heart Failure Index were associated with: reduced left ventricular ejection fraction (p=0.001), longer time of experience with the disease (p=0.05) and joint monitoring by physician and nurse (p=0.007).Conclusion: investments are needed to improve the self-care behavior and the nursing can play a relevant role in this improvement.